Cosmology of Labuhan Larung Sesaji Ritual Meaning the Homogeneity Strategic Cost Concept in Blue Sea Fisheries Accounting - Whedy Prasetyo (JASF: Journal of Accounting and Strategic Finance, 2022)
Research to reveal the formation of fishermen’s income based on homogeneity strategic cost concept is shown in the labuhan larung sesaji ritual cosmology. This concept gives meaning to the presence of blue sea fisheries accounting. Qualitative methods with a phenomenological approach are used in this study. The results show the homogeneity strategic cost that all stages of labuhan larung sesaji ritual activity or the elements in it (represented by costs) have the same position or importance in generating income. On the basis of this idea, all stages of ritual activities contribute or contribute to fishermen’s income creation of in proportion to costs. So, if amount of costs for ritual activities have occurred, then in fact amount of revenues have been formed or collected, the amount of which is in accordance with income and costs ratio. The homogeneity strategic costs concept contributes to interpreting the presence of blue sea fisheries accounting based on sustainability of marine living resources and fish catches. Accounting based on open access resources, and marine sustainability as marine biota for logistical growth of fish stocks or populations without operating costs for pisciculture.